Copper-promoted hydration and annulation of 2-fluorophenylacetylene derivatives: from alkynes to benzo[b]furans and benzo[b]thiophenes - Li, Yibiao; Cheng, Liang; Liu, Xiaohang; Li, Bin; Sun, Ning (Beilstein Journal of Organic Chemistry, 2014)
An efficient copper-promoted hydration reaction and its application in the synthesis of benzo[b]furan and benzo[b]thiophene derivatives is presented starting from readily available 2-fluorophenylacetylene derivatives. The key annulation step involves the hydration of the C–F bond of 2-fluorophenylacetylene derivatives followed by an intramolecular annulation to afford benzo[b]furan and benzo[b]thiophene derivatives. Moreover, structurally important 2,2'-bisbenzofuran scaffolds are provided in good yields.
Keywords: annulation; benzo[b]furan; C–F activation; copper-promoted; heterocycle